ANALISIS KESULITAN BELAJAR MATEMATIKA PADA POKOK BAHASAN BANGUN RUANG PADA SISWA KELAS IV SD NEGERI 138 BASOKENG KABUPATEN BULUKUMBA - Erwin Nurdiansyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2018)
Abstract: Mathematics Learning Difficulty Analysis for Building Space Subjects for Class IV Students of 138 Elementary School Basokeng, Bontotiro District, Bulukumba Regency. The purpose of this study was to determine the level of difficulty of grade IV students of SD Negeri 138 Basokeng, Bulukumba Regency in describing sketches of building space, mentioning parts of a building space, describing the nets of a building space, and knowing the factors of learning difficulties of fourth grade students 138 Basokeng Public Elementary School, Bulukumba Regency in solving the problems of building space. This type of research is descriptive qualitative research and this research variable is the difficulty of fourth grade students of SD Negeri 138 Basokeng, Bulukumba Regency in learning mathematics on the subject of building space. The location in this study was 138 Public Elementary School Basokeng and the subject was all fourth grade students of 138 Basokeng Public Elementary School, Bulukumba, in the year 2017-2018, which amounted to 16 people. The instruments and data collection techniques in this study are learning outcomes tests and interview guidelines. The results showed the percentage score of difficulty in drawing sketches of space was 60.93%, the difficulty was categorized as